Zwischen Sozialdisziplinierung und magischer Reputation: Trickkünstler und ihre Performanzen im 16. Jahrhundert - Reich, Philip (Daphnis, 2025)
Abstract In the 16th century, the figure of the conjurer assumed increasing importance as a social phenomenon, though his representation was consistently refracted through criminological lenses. This article fathoms the cultural significance of conjurers and their performances, beginning with the early modern demonological discourse, in which the art of illusion is closely associated with - though not synonymous with - demonic deception. Within this context, magical performances are frequently instrumentalized for ideological or disciplinary purposes, and trickery was broadly construed as deviant, subjecting its practitioners to mechanisms of social control. Against this backdrop, the article presents two case studies: the first reconstructs the figure of the street conjurer by juxtaposing the Liber Vagatorum with selected Styrian police records; the second contrasts the apprehended and convicted Styrian fraudsters with the remarkable career of Hieronimo Scotto, who secured the patronage of Europe’s highest nobility through his card tricks, but ultimately fell victim to scandal and political intrigue. Together, these examples reveal how performances of illusion intersected with power, suspicion, and social order in early modern Europe.